High sensitive optical fiber SPR sensor for label-free detection of Staphylococcus aureus - Wang, Jiale; Zhao, Chao; Zhu, Jiayi; Xia, Binyun; Wang, Ning; Chen, Xi; Niu, Kunpeng; Hou, Jianguo; Jing, Xinyue; Zhou, Hang; Zhuang, Ziyang; Lei, Lei (Microchemical journal, 2024)
[Display omitted] •An optical fiber bacterial sensor is fabricated with selective detection of Staphylococcus aureus.•The goat anti-human immunoglobulin G (IgG) antibody was used to detect bacteria specifically.•Detection sensitivity of 2.19 nm/ (log CFU/mL) and detection limits of 1.18 CFU/ml Staphylococcus aureus was achieved.•The optical fiber bacterial sensor shows excellent specificity and stability. Optical fiber bacterial sensors have attracted attention in many fields due to their unique advantages. However, it is still difficult to promote its practicality which is mainly subject to their low sensitivity, inferior stability, and reliability. This work reported here an optical fiber surface plasmon resonance (SPR) biosensor enhanced by gold nanoparticles (AuNPs)/Au film coupling for label-free detection the Staphylococcus aureus (S. aureus), while both the gold substrates were successfully biofunctionalized with goat anti-human immunoglobulin G (IgG) as the probe to capture and detect the bacteria. In the experiment, the refractive index（RI） sensitivity of the Multimode-Singlemode-Multimode optical fiber (MSMOF) coated with Au film was improved by 19 % after the AuNPs were homogeneously decorated on the Au film surface. To detect S. aureus by the sensor, the SPR wavelength variation in the transmission spectrum was recorded, and its limit of detection (LOD) was demonstrated experimentally to be about 50 CFU/mL and was obtained theoretically to be 1.18 CFU/mL during its concentration range of 50–108 CFU/mL. Also, it shows great linearity in the range of 102-108 CFU/mL and the sensor exhibits excellent specificity and stability. This kind of SPR-enhanced optical fiber biosensor is fully promising for its applications in biomedicine, food safety, pharmaceuticals, etc.